Enhanced adhesion between polycarbonate substrates and tin-doped indium oxide films by ion-assisted reaction - Cho, JS; Koh, SK (ELSEVIER SCIENCE BV, 2001)
Adhesion between polycarbonate (PC) substrates and tin-doped indium oxide (TTO) films was improved by an ion-assisted reaction (IAR) process in which the PC surfaces were irradiated by 1 keV Ar+ ions in oxygen gas environment. The dose of Ar+ ions was changed from 5 x 10(14) to 5 X 10(16) ions/cm(2) and the oxygen gas with a flow rate of 4 seem (ml/min) was introduced near the PC surfaces during Ar+ ion irradiation. After TAR treatment, the contact angles of the PC surfaces to water were changed from 78 degrees to 12 degrees and those to formamide from 63 degrees to 5 degrees. X-ray photoelectron spectroscopy analysis showed that hydrophilic groups were formed on the modified PC surfaces by a chemical reaction between the unstable chains induced by the ion irradiation and the oxygen gas, and the newly formed hydrophilic group was identified as -(C=O)- bond (carbonyl group). The surface energy of the modified PC surfaces increased mainly due to the polar component related to the hydrophilic group. Based on these results, a mechanism of adhesion improvement for the ITO IPC system was proposed. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: IRRADIATION; ENVIRONMENT; MICROSTRUCTURE